Magnitude and factors associated with nonadherence to antiepileptic drug treatment in Africa: A cross‐sectional multisite study. Issue 2 (30th March 2017) - Ibinda, Fredrick; Odermatt, Peter; Kariuki, Symon M.; Kakooza‐Mwesige, Angelina; Wagner, Ryan G.; Owusu‐Agyei, Seth; Masanja, Honorati; Ngugi, Anthony K.; Mbuba, Caroline K.; Doku, Victor C. K.; Neville, Brian G.; Sander, Josemir W.; et al.
Summary: Objectives: The epilepsy treatment gap is large in low‐ and middle‐income countries, but the reasons behind nonadherence to treatment with antiepileptic drugs (AEDs) across African countries remain unclear. We investigated the extent to which AEDs are not taken and associated factors in people with active convulsive epilepsy (ACE) identified in cross‐sectional studies conducted in five African countries. Methods: We approached 2, 192 people with a confirmed diagnosis of ACE for consent to give blood voluntarily. Participants were asked if they were taking AEDs, and plasma drug concentrations were measured using a fluorescence polarization immunoassay analyzer. Information about possible risk factors was collected using questionnaire‐based clinical interviews. We determined factors associated with nonadherence to AED treatment in children and adults, as measured by detectable and optimal levels, using multilevel logistic regression. Results: In 1, 303 samples assayed (43.7% were children), AEDs were detected in 482, but only 287 had optimal levels. Of the 1, 303 samples, 532 (40.8%) were from people who had reported they were on AEDs. The overall prevalence of nonadherence to treatment was 63.1% (95% confidence interval [CI] 60.5–65.6%) as measured by detectable AED levels and 79.1% (95% CI 73.3–84.3%) as measured by optimal AED levels; self‐reported nonadherence was 65.1% (95% CI 45.0–79.5%). Nonadherence was significantly (p < 0.001) more common among the children than among adults for optimal and detectable levels of AEDs, as was the self‐reported nonadherence. In children, lack of previous hospitalization and learning difficulties were independently associated with nonadherence to treatment. In adults, history of delivery at home, absence of burn marks, and not seeking traditional medicine were independently associated with the nonadherence to AED treatment. Significance: Only about 20% of people with epilepsy benefit fully from antiepileptic drugs in sub‐Saharan Africa, according to optimum AEDs levels. Children taking AEDs should be supervised to promote compliance.